2017
DOI: 10.21767/amj.2017.3196
|View full text |Cite
|
Sign up to set email alerts
|

Use of optical magnification and microsurgical technique in general surgery

Abstract: EDITORIALPlease cite this paper as: D'Orazi V, Ortensi A. Use of optical magnification and microsurgical technique in general surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Nevertheless, no association was shown in our series between the rate of perioperative complications and the complexity or duration of the operation. We strongly believe that total thyroidectomy performed by experienced surgeons with microsurgical technique under optical magnification permits to significantly reduce the incidence of permanent hypoparathyroidism and RLN lesions, as already demonstrated in our previous studies and confirmed by numerous evidences in the literature [35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, no association was shown in our series between the rate of perioperative complications and the complexity or duration of the operation. We strongly believe that total thyroidectomy performed by experienced surgeons with microsurgical technique under optical magnification permits to significantly reduce the incidence of permanent hypoparathyroidism and RLN lesions, as already demonstrated in our previous studies and confirmed by numerous evidences in the literature [35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, using magnifying loupes in thyroid surgery is advocated to increase the surgeon’s precision. Additionally, the above anatomical structures could be easily identified during surgery 6 . The first surgical application of the loupe procedure in thyroid surgery was reported by Atti and Khafif in 1975 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a microsurgical approach in thyroid surgery by using magnifying loupes or surgical microscope is believed to enhance the surgeon’s precision. Also, it was stated that the above anatomical structures could be identified in an easier way during the operation [3]. The first microsurgical thyroidectomy was reported in 1975 by Atti et al [4].…”
Section: Introductionmentioning
confidence: 99%